Under nutrition among Chepang children of Chitwan, Nepal - Dhungel, Kshitiz Upadhyay; Shakya, Nikita (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: Under nutrition, which includes wasting (low weight-for-height), stunting (low height-for-age) and underweight (low weight-for-age) makes children in particular much more vulnerable to disease and death. This research analyzes the nutrition status of the Chepang children (an indigenous Tibeto-Burman ethnic group of the Mahabharat mountain range of central Nepal living semi-nomadic life) and the associated demographic factors affecting it. Material and Methods: This study is carried out in children of chepang community living in Kalika municipality, Chitwan, Nepal. The children were interviewed together with their parents/ teachers after which their anthropometric measurements were taken. Information regarding socio – demographic information, physical activities and diet intake were recorded. Food frequency questionnaire was utilized to know the frequency of food per week. Face-to-face interview technique with a structured questionnaire was used to collect data from the respondents. Results: Out of the 145 children, 72.3% of children were found to be underweight and 86.9% stunted whereas comparatively lower amount of children were found to be wasted (6.2%). Nearly half of the children (43.5%) under 5 years of age were found to be at a risk for acute malnutrition. Conclusions: Majority of the children were underweight. More than half of the total children were found to be stunted and underweight where as few numbers of the children were found to be wasted.